2009
DOI: 10.1071/ea08210
|View full text |Cite
|
Sign up to set email alerts
|

A chemical analysis of samples of crude glycerol from the production of biodiesel in Australia, and the effects of feeding crude glycerol to growing-finishing pigs on performance, plasma metabolites and meat quality at slaughter

Abstract: The aims of this study were to: (i) determine the chemical composition of 11 samples of crude glycerol collected from seven Australian biodiesel manufacturers; and (ii) examine the effects of increasing levels of crude glycerol fed to growing-finishing pigs on performance, plasma metabolites and meat quality at slaughter. Chemical composition of crude glycerol samples varied considerably; glycerol content ranged between 38 and 96%, with some samples containing up to 29% ash and 14% methanol. One of these sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
5
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 15 publications
14
102
5
9
Order By: Relevance
“…The study of Lammers et al (2) evaluated crude glycerin in growing pigs and described animal growth, feed intake, conversion, fat in the 10 th rib, loin area and free fat percentage showing no effects due to treatments, similarly to the results found in the present study. Contrary, in piglets, the inclusion of crude glycerin improved average daily gain in linear form, without affecting consumption and conversion (16) , similar to the results obtained with 8% glycerol in diet (10) and growing pigs (8) .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The study of Lammers et al (2) evaluated crude glycerin in growing pigs and described animal growth, feed intake, conversion, fat in the 10 th rib, loin area and free fat percentage showing no effects due to treatments, similarly to the results found in the present study. Contrary, in piglets, the inclusion of crude glycerin improved average daily gain in linear form, without affecting consumption and conversion (16) , similar to the results obtained with 8% glycerol in diet (10) and growing pigs (8) .…”
Section: Resultssupporting
confidence: 63%
“…Table 1 displays the chemical composition of crude glycerin from PO. The maximum level of inclusion of CG was 10% because it is the level that has not affected the performance of pigs using other sources of crude glycerin (2,6,7,9,10) , although in Australia the use of up to 16% of CG did not affect the performance of animals but there were difficulties in feed management (8) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, previous studies on glycerin in the diets of growing-finishing pigs found no differences between treatments in insulin , cortisol (Lammers et al, 2008a) or glucose (Hansen et al, 2009). Likewise, Schieck et al (2010a) found that increasing crude glycerin levels in the diet of lactating sows had no effect on plasma glucose.…”
Section: Discussionmentioning
confidence: 71%
“…Products with lower purity, as in the case of crude glycerol, may present contaminants originating from the extraction process, such as methanol, a toxic substance which is considered unsafe at levels above 150 ppm (Dasari 2007). However, pigs fed diets containing glycerol and 2,900 ppm (Hansen et al 2009) and3,200 ppm (Lammers et al 2008) of methanol showed no signs of intoxication. Out of the 17 studies used in this review, seven (41%) used glycerol with purity between 65 and 90%; seven (41%) reported the use of glycerol between 90% and 99.7% purity and three (18%) used products with a purity greater than 99.7%.…”
Section: Resultsmentioning
confidence: 99%